Impacts of mitochondrial dysfunction on axonal microtubule bundles as a potential mechanism of neurodegeneration - Murray-Cors, Scott; Owens, Milli; Liew, Yu-Ting; Day, Maureece; Cairns, William; Prokop, Andreas (Frontiers in Neuroscience, 2025)
Mitochondrial dysfunction is an important cause for neurodegeneration, often associated with dyshomeostasis of reactive oxygen species, i.e., oxidative stress. However, apart from ATP production, mitochondria have many other functions the aberration of which may impact neurons in very different ways. Oxidative stress can cause the deterioration of axonal microtubule bundles, thus critically affecting the highways for life-sustaining transport and providing a potential path to neurodegeneration. We recently found that aberrant transport of mitochondria can have this effect by causing oxidative stress. We therefore asked which aberrations of mitochondrial physiology might impact microtubules, which of these might explain the observed consequences of aberrant mitochondrial transport, and whether mitochondria-induced microtubule phenotypes are always mediated by oxidative stress. Using one consistent Drosophila primary neuron system, we studied functional loss of 13 different mitochondrial factors known to be detrimental to neurons in vivo. Losses of five factors caused MT damage, namely pyruvate dehydrogenase A, succinate dehydrogenase A, adenine nucleotide translocase, frataxin and superoxide dismutase 2. All involved oxidative stress, hence supported the path from mitochondria via oxidative stress to microtubule deterioration; of these, we discuss superoxide dismutase 2 as potential candidate explaining effects of mitochondrial transport aberration. Six of the remaining factors not causing microtubule damage were important mitochondrial morphogenesis regulators, suggesting efficient protection mechanisms preventing oxidative stress upon mitochondrial contortion.